Implementing Robust Estimation Instruments for Panel Data Regression Models with Errors-in-Variables - Racicot, François-Éric (Université d'Ottawa | University of Ottawa, 2015)
Keywords: EViews code; fixed effects; GMM; panel data; random effects; robust instruments.
Le texte intégral de ce document de travail n''est pas disponible en ligne. Pour plus de renseignements sur ce document, veuillez communiquer avec la Direction de la recherche de l''École de gestion Telfer. The full text of this working paper is not available online. For more information regarding this working paper, please contact the Telfer School of Management Research Office.